2005
DOI: 10.2320/matertrans.46.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus on Sulfide Precipitation in Strip Casting Low Carbon Steel

Abstract: The effect of phosphorus addition on sulfide precipitation for strip casting low carbon steel containing copper was investigated and discussed with respect to the morphology, size, and composition of sulfide. Both experimental results and mathematical calculation showed that the addition of phosphorus retards the sulfide precipitation at high temperature, promotes the supersaturation of sulfur, and produces more copper bearings and smaller sulfides at low temperature. Phosphorus also promotes sulfide precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Both the starting and finishing temperatures of the MPS are higher than those of the LPS sample, which are caused by the increase in the T A3 temperature that occurred by the phosphorous addition as analyzed by Yoshida 4,5) and Liu. 7) This becomes more apparent at the rapid cooling rate as shown in Fig. 10. …”
Section: G G → → a A Transformationmentioning
confidence: 58%
See 3 more Smart Citations
“…Both the starting and finishing temperatures of the MPS are higher than those of the LPS sample, which are caused by the increase in the T A3 temperature that occurred by the phosphorous addition as analyzed by Yoshida 4,5) and Liu. 7) This becomes more apparent at the rapid cooling rate as shown in Fig. 10. …”
Section: G G → → a A Transformationmentioning
confidence: 58%
“…Thus, the concentration of phosphorus and sulfur in the dphase may become very high in the final stage of the d /g transformation. Yoshida 4) and Liu 7) presented a detailed discussion on the effects of phosphorus on the d /g transformation and the g /a transformation based on the phase diagram and thermodynamic calculation. In brief, phosphorus could greatly reduce the T A4 temperature and increase the T A3 temperature under the equilibrium condition.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous papers, 13,20,21) the authors found that copper sulfides could be formed in strip casting steel. Differently from the formerly reported copper sulfides in steel/iron, [14][15][16][17][18][19] which usually coexisted with MnS, almost pure copper sulfides were found in the present strip casting steels.…”
Section: Introductionmentioning
confidence: 99%